PENGARUH SUMBER DAYA MANUSIA, KETERSEDIAAN INFRASTRUKTUR, KOMITMEN PIMPINAN, DAN KETELADANAN PIMPINAN TERHADAP TINGKAT MATURITAS SISTEM PENGENDALIAN INTERN PEMERINTAH (STUDI PADA PEMERINTAH DAERAH KABUPATEN INDRAGIRI HULU) - Suryatin Suryatin; Rita Anugerah; Novita Indrawati (PEKBIS, 2019)
This study aims to know and analyze the effect of human resources, the availabilityof infrastructure, the leader’s commitment and the exemplary of leader on MaturityLevel of SPIP of local government of Indragiri Hulu regency. To test thehypothesized, the Structural Equation Modeling (SEM) analysis is applied toquestionnaire survey data from 184 respondents of Local Government of IndragiriHulu Regency. As hypothesized the human resources, Commitment and exemplaryHof leader effect to maturity level of SPIP. However this study failed to show theeffect of availability of infrastructure on maturity level of SPIP